Validity of irritability in Huntington's disease: A scoping review. (November 2019) - Simpson, Jane; Dale, Maria; Theed, Rachael; Gunn, Sarah; Zarotti, Nicolò; Eccles, Fiona J.R.
Abstract: Purpose: To scope the literature concerning irritability in Huntington's disease to determine whether or not irritability is a valid and meaningful construct within this population. Method: A scoping literature review was conducted based on findings from a search of five databases (Academic Search Ultimate, PsycINFO, CINAHL, Scopus and Web of Science) in November 2018. From an initial return of 453 papers, 40 were found suitable for review. Results: Review of the 40 studies highlighted several aspects of irritability in people with HD which influence its validity as an independent construct in context of the disease. While various measures are used to assess irritability, a gold standard has yet to be identified and consequently irritability is assessed inconsistently across the literature. In addition, the results suggest that irritability may not reflect pathological disease processes in HD, but rather comprises a multidimensional construct which appears to be strongly associated with other psychological difficulties such as depression and anxiety. Conclusions: The current concept of irritability in people with HD continues to lack a general consensus in the clinical literature, in terms of both operationalisation and assessment. Consequently, further research is warranted in order to determine the extent to which irritability is a valid construct within the context of HD, including its associated behavioural, cognitive and affective dimensions.